Partially replacing dietary fish meal by Saccharomyces cerevisiae culture improve growth performance, immunity, disease resistance, composition and function of intestinal microbiota in channel catfish (Ictalurus punctatus). Issue 125 (June 2022) - Hao, Qiang; Xia, Rui; Zhang, Qingshuang; Xie, Yadong; Ran, Chao; Yang, Yalin; Zhou, Wenhao; Chu, Fuwei; Zhang, Xiaomei; Wang, Yu; Zhang, Zhen; Zhou, Zhigang
Abstract: The aim of the present study was to investigate the partial replacement of fish meal by Saccharomyces cerevisiae culture on growth performance, immunity, composition and function of intestinal microbiota and disease resistance in channel catfish ( Ictalurus punctatus ). Two equal nitrogen and energy diets were prepared including a basal diet (containing 10% fish meal, Control) and an experimental diet (replacing 20% of the fish meal of the basal diet with yeast culture, RFM). Channel catfish were fed with the diets for 12 weeks. The results showed that weight gain and condition factor were significantly increased, and FCR was significantly decreased in RFM group (P < 0.05). The gene expression of intestinal HIF1α was significantly increased in RFM group ( P  < 0.05), while the expressions of NF-κB in the intestine and liver were significantly decreased ( P  < 0.05). The relative abundance of Firmicutes tended to increase, and the Turicibacter had an upward trend (0.05 <  P  < 0.2). In addition, the survival rate of channel catfish was significantly increased in RFM group after challenged with Aeromonas veronii Hm091 and Aeromonas hydrophila NJ-1 ( P  < 0.05). Compared with intestinal microbiota of channel catfish of control group, intestinal microbiota of channel catfish of RFM group significantly increased the expression of HIF1α, and decreased the expression of IL-1β and TNF-α ( P  < 0.05) in germ-free zebrafish . Intestinal microbiota induced by RFM diet also significantly increased disease resistance to Aeromonas veronii Hm091 and Aeromonas hydrophila NJ-1. In conclusion, replacement of fish meal by the yeast culture improved the growth, immunity and disease resistance of channel catfish, and intestinal microbiota of channel catfish induced by the yeast culture played a critical role in these effects. Highlights: RFM diet increased growth performance, gut and liver health of channel catfish. RFM diet enhanced the resistance of channel catfish to A. Veronii and A. hydrophila. Intestinal microbiota induced by RFM diet played a critical role in probiotic effects of Saccharomyces cerevisiae by using the germ-free zebrafish model.